The intellectual architect in intermediate cities. Reflections between networks and spaces of culture of the twentieth century - Blanc, Maria Claudina; Cattaneo, Daniela (Estoa. Journal of the Faculty of Architecture and Urbanism, 2020)
Including the architect in intellectual history studies is a relatively recent approach. From there, it is proposed to address the role of these professionals in their relation to cultural spaces in the 20th century and their impact on the social and material transformation of the city, attending to intermediate scales and regional urban logics. It is worked on this key with two architects, in two moments, in the city of Rosario, Argentina: Hilarión Hernández Larguía (1892-1978) and Horacio Quiroga (1941); focusing, from the spatial and urban key, on the specificity and mutations in time of the cultural networks in which these educated technicians interact and their possible feedbacks. From two projects of cultural and educational institutions in which they participate, the articulation between architectural designs and the functions that their authors carried out beyond disciplinary purposes are addressed; also, the relationship between the urban dimension of their actions. The complexity of the incumbencies and the relational plot of these architects shows the turns in the professional profiles from particular geographical-cultural junctures.